Hubungan antara Tekanan Teman Sebaya dan Kejadian Bullying pada Remaja - Salsa Aisyah; Taty Hernawaty; Ryan Hara Permana; Sukma Senjaya (Universitas Faletehan, 2025)
Aggressive behavior among peers is currently gaining renewed attention within educational institutions. Peers exerting negative pressure can influence deviant behavior, one of which is bullying. The purpose of this study was to determine the relationship between peer pressure and the incidence of bullying among adolescents at SMP X. This study employed a quantitative correlational design with a cross-sectional approach. The study population comprised all adolescents at SMP X, totaling 1.047 individuals. The sample was drawn using the Slovin formula with the proportionate stratified random sampling technique, resulting in a minimum sample size of 289 individuals. Data collection utilized the peer pressure inventory and the adolescent peer relations instrument questionnaires, which were then analyzed using the Spearman rank test with the SPSS application. The results indicated that the incidence of bullying among adolescents was in the high category (54%), with a similarly high level of peer pressure (53%). Furthermore, there was a relationship between peer pressure and bullying incidence among adolescents (p=0.000) with a positive direction and a weak correlation between the variables (r=0.285). The incidence of bullying among adolescents in the school environment was influenced by peer factors. New strategies from various parties were expected to be developed to prevent bullying among adolescents.